PENINGKATAN KEMAMPUAN GURU ENGINTEGRASIKAN LITERASI DALAM PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SMA NEGERI 1 GAROGA SEMESTER 1 TAHUN PELAJARAN 2022/2023 - Bosar Sormin (Hijri, 2023)
The low ability of teachers to integrate literacy into learning at SMAN 1 Garoga is a fundamental problem for improving teacher professionalism in developing a literacy culture. Efforts are made is the implementation of academic supervision. The research subjects were 8 teachers at SMAN 1 Garoga. Methods of data collection using observation and documentation techniques. Data validation with triangulation techniques. The assessment uses 2 observation sheets, namely observation of discussion activities and observation of teacher activities in integrating literacy in learning. The results showed that in the discussion activities in the initial conditions there was 1 person (12.50%) who was declared complete, in the first cycle it increased to 4 teachers or 50.00% and in the last cycle to 8 teachers or 100% with 3 teachers' explanation ( 37.50%) in very good criteria and 5 teachers (62.50%) in good assessment criteria. Assessment of teacher improvement in integrating literacy into learning in the initial conditions of 8 teachers, none of the teachers were declared complete. In the first cycle there were 3 teachers or 37.50% who were declared complete. In the second cycle, 8 teachers (100%) were declared complete with an explanation of 2 teachers (25.00%) in very good assessment criteria and 6 teachers (75.00%) in good assessment criteria. From the explanation above, it can be concluded that through the implementation of academic supervision at SMAN 1 Garoga it is proven to be able to improve the teacher's ability to integrate literacy in learning.Keywords: Supervisi Akademik, Kemampuan, Literasi, Pembelajaran